Manajemen Pemuatan Barang Berbahaya untuk Keselamatan Kapal Muatan dan ABK: Indonesia - B. L Hentri Widodo; Eni Tri Wahyuni; M. Aji Luhur (PPPM Polimarin, 2023)
This study aims to know and understand the labels of aged cargo labels, understand the handling of hazardous cargo on board, and understand the principles of loading principles in relation to the protection of ships, mautan and crew and also know about handling fires caused by hazardous cargo on board and handling patterns in the event of a fire caused by hazardous cargo. The impact arises due to the crew not understanding the labels of dangerous mautan, as well as the arrangement or placement of cargo in containers that do not pay attention to the segregation table that has been regulated in the IMDG Code. Causing cargo to be contaminated, causing fires, container leaks. Meanwhile, if in the loading process does not correctly understand the loading principles that exist, especially in the loading of dangerous goods. It needs special handling that will endanger the ship, cargo, even the crew of the ship itself. The role and understanding of the dangerous cargo of the crew, especially the skipper and the first crew responsible for the loading of the sangant, is important. Both during loading preparation by making a loading plan, during loading, and during unloading. Literature and documentation studies, as well as descriptive data in the form of writings from several sources. The results of the discussion can be concluded even maximum loading management such as the preparation of loading plans, loading that pays attention to the segregation table by referring to the nature of dangerous goods in accordance with the good IMDG Code when loading loads in large quantities in the container carried out by the crew will be achieved shipping safety, ship safety, cargo and also the crew itself. The pattern of handling emergencies when the ship contains good dangerous cargo, by referring to the IMDG Code and Emergency Response Guidebook (ERG) will be able to minimize property losses, namely ship damage, cargo damage, and even life losses can be minimized. Shipping safety is the main objective that we want to achieve in every freight shipping operation including dangerous goods cargo.